G.W. Samson family papers - Samson, G. W. (George Whitefield), 1819-1896.
Chiefly family correspondence of and relating to members of the Kenrick (Kendrick), Samson, and Smallwood families. Correspondents include Enoch B. Kenrick, William Kenrick, Elizabeth Smallwood Samson, and Mehetabel Kenrick Samson.
Clergyman, pastor of the E Street Baptist Church, and president of Columbian College, both in Washington, D.C.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Kenrick, Enoch B. -- Correspondence; Kenrick, William, -- 1789-1872 -- Correspondence; Kendrick family; Samson, Elizabeth Smallwood -- Correspondence; Samson, Mehetabel Kenrick -- Correspondence; Sampson family; Smallwood family; E Street Baptist Church (Washington, D.C.); Columbian College in the District of Columbia; Baptists -- Washington (D.C.); Clergy; College presidents